Acute kidney injury increases risk of kidney stones—a retrospective propensity score matched cohort study. Issue 1 (2nd February 2022) - Cheikh Hassan, Hicham I; Murali, Karumathil; Lambert, Kelly; Lonergan, Maureen; McAlister, Brendan; Suesse, Thomas; Mullan, Judy
ABSTRACT: Background: Acute kidney injury (AKI) is common. An episode of AKI may modify the risk of developing kidney stones by potential long-term effects on urine composition. We aimed to investigate the association between AKI and the risk of kidney stone presentations. Methods: The retrospective cohort study used patient data (1 January 2008–31 December 2017), from an Australian Local Health District, which included AKI diagnosis, demographics, comorbidities and kidney stone admissions. Time-varying Cox proportional hazards and propensity-matched analysis were used to determine the impact of AKI on the risk of kidney stones. To address possible population inhomogeneity in comparisons between no AKI and hospitalized AKI, sub-group analysis was done comparing inpatient and outpatient AKI versus no AKI, to assess consistency of association with future stones. Sensitivity analysis was undertaken to capture the impact of a known AKI status and AKI severity. Results: Out of 137 635 patients, 23 001 (17%) had an AKI diagnosis and 2295 (2%) had kidney stone presentations. In the unadjusted analysis, AKI was associated with kidney stones, with AKI used as a time-varying exposure, [hazard ratio (HR) 1.32, 95% confidence interval (CI) 1.16–1.50)]. Both inpatient-AKI (HR 1.19, 95% CI 1.01–1.39) and outpatient-AKI (HR 1.59, 95% CI 1.30–1.94) were significantly associated with future stones compared to no AKI subjects. This association persisted in the adjusted analysis (HR 1.45, 95% CI 1.26–1.66), propensity-matched dataset (HR 1.67, 95% CI 1.40–1.99) and sensitivity analysis. There was a dose-response relationship with higher stages of AKI being associated with a greater risk of kidney stones. Conclusions: In a large cohort of patients, AKI is associated with a greater risk of kidney stones, which increases with higher stages of AKI. This association should be examined in other cohorts and populations for verification. Graphical Abstract: